Оценка динамики объемов добычи газа из месторождений на завершающей стадии разработки - Братах, Михаил Иванович; Варавина, Елена Павловна; Кутя, Михаил Михайлович; Ткач, В. А. (НТУ "ХПИ", 2013)
Розроблено та реалізовано для практичних цілей математичну модель динаміки обсягів видобутку газу для родовищ на завершальній стадії розробки, оцінено вплив утворення рідинних пробок в ліфтових трубах свердловини та в порожнині її шлейфа на режими роботи системи "свердловина–шлейф–установка збору".

In the article a mathematical model of the gas production dynamics for fields in the final stages of development are developed and implemented for practical purposes. Also authors estimated the effect of liquid plugs creation in the tubing of the well and in the cavity of its field line on modes of the system "well–field line–collecting unit".
The estimation of gas production dynamics for field in the final stages of development
Keywords: газодобывающая промышленность; скважины; добыча углеводородов; природный газ; система добычи газа